Comparison of in vitro and in vivo binding site competition of Bacillus thuringiensis Cry1 proteins in two important maize pests. Issue 4 (8th January 2022) - Hernández‐Martínez, Patricia; Bretsnyder, Eric C; Baum, James A; Haas, Jeff A; Head, Graham P; Jerga, Agoston; Ferré, Juan
Abstract: BACKGROUND: Binding site models, derived from in vitro competition binding studies, have been widely used for predicting potential cross‐resistance among insecticidal proteins from Bacillus thuringiensis . However, because discrepancies have been found between binding data and observed cross‐resistance patterns in some insect species, new tools are required to study the functional relevance of the shared binding sites. RESULTS: Here, an in vivo approach has been applied to the competition studies to establish the functional relevance of shared binding sites as determined by in vitro competition assays. Using Cry disabled proteins as competitors in mixed protein overlay assays, we assessed the preference of Cry1Ab, Cry1Fa, and Cry1A.105 proteins for shared binding sites in vivo in two important corn pests, Ostrinia nubilalis and Spodoptera frugiperda . CONCLUSION: This study shows that in vivo and in vitro binding site competition assays can provide useful information to better ascertain whether different Cry proteins share binding sites and, consequently, whether cross‐resistance due to binding site alteration can occur. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : In vivo and in vitro binding site competition assays can provide useful information to ascertain whether different Cry proteins share binding sites and, consequently, whether cross‐resistance can occur.